Características clínicas e microbiológicas de adultos jovens de uma amostra representativa da área rural do Sul do Brasil: estudo epidemiológico - Boligon, Jociana (2017)
The present thesis is composed by two scientific articles, whose main theme refers to the periodontal disease in young adults of a Brazilian rural area. Article 1: Periodontitis in young adults living in the rural area of southern Brazil: a cross-sectional study. The objective of this study was to describe the prevalence, extent and severity of periodontitis in young adults from a representative sample of 171 individuals, aged 15-35 years, rural residents. Six sites per tooth were clinically evaluated. Three diagnostic criteria were used to classify individuals as to their periodontal condition. The highest percentage of plaque retentive factor (31.07 ± 3.15), mean clinical insertion level (2.08 ± 0.14), dental loss and smokers (16.6%) were observed in older individuals (26-35 years). The prevalence and extent of periodontal disease when assessed according to severity was twice as high in subjects with severe periodontitis (7.42 ± 1.03) compared to the moderate form (3.28 ± 0, 54) or mild (3.74 ± 0.27). Race (p = 0.022) and smoking (p=0.012) were associated with increased prevalence of aggressive periodontitis. In this study, the results show a high prevalence of periodontitis affecting non-white young adults and smokers living in rural areas of southern Brazil. Article 2: Profile of subgingival microbiota in young adults living in rural areas of southern Brazil: a cross-sectional study. This work aimed to describe the subgengival microbiological profile of young adults based on the criteria of periodontal diagnosis of the modified CDC / AAP. One hundred and ten individuals aged 15-30 years underwent complete periodontal clinical examination, and subgingival biofilm samples were collected at four sites per individual. Analyzes for the detection of 45 oral and non-buccal bacterial species were performed by the Checkerboard DNA DNA hybridization technique. High frequency and counts of oral and non-oral microbial species were observed in the sample, regardless of periodontal clinical diagnosis. Microbial counts were higher at sites deep than shallow; However, sites with bleeding probing showed a higher percentage of bacteria of the orange and red complexes and of Aggregatibacter actinomycentecomitans.